A 1-Month Physical Therapy–Based Outpatient Program for Adults Awaiting Lung Transplantation: A Retrospective Analysis of Exercise Capacity, Symptoms, and Quality of Life. Issue 2 (April 2019) - Byrd, Rebecca; Smith, Patrick; Mohamedaly, Omar; Snyder, Laurie D.; Pastva, Amy M.
Abstract : Purpose: Rehabilitation can improve health outcomes in candidates for lung transplantation. The purpose of this study was to retrospectively evaluate the effect of a 1-month physical therapy (PT)–based outpatient program on exercise capacity, symptoms, quality of life (QOL) and examine predictors of functional outcome changes in adults awaiting lung transplantation. Methods: Participants (n = 141) completed a 23-session exercise and educational program over 1 month. Outcomes included 6-minute walk distance (6MWD), San Diego shortness of breath questionnaire (SOBQ), Center for Epidemiological Studies-Depression Scale (CESD), and Ferrans and Powers QOL Index Pulmonary Version III. Results: Participants were older (median age 63) with restrictive (59%) or obstructive (24%) disease. Moderate-to-large improvements in 6MWD were observed (69 m, P < .001, d = 0.72), independent of demographics, symptoms, and QOL. Lower initial 6MWD and lower oxygen utilization were associated with greater 6MWD improvements, with largest gains occurring in initial 6MWD <305 m. Small-to-moderate improvements were observed on CESD ( P < .001, d = 0.26) and in overall QOL ( P < .001, d = 0.27), with a nonsignificant improvement observed on SOBQ ( P = .248, d = 0.13). Conclusions: Completion of a 1-month PT-based outpatient rehabilitation program was associated with improved exercise capacity, depressive symptoms, and QOL.